Pacing in congenital heart disease – A four-decade experience in a single tertiary centre. (15th August 2017) - Midha, Disha; Chen, Zhong; Jones, David G.; Williams, Howell J.; Lascelles, Karen; Jarman, Julian; Clague, Jonathan; Till, Janice; Dimopoulos, Konstatinos; Babu-Narayan, Sonya V.; Markides, Vias; Gatzoulis, Michael A.; et al.
Abstract: Background: The increased risk of brady- and tachy-arrhythmias in the congenital heart disease (CHD) population means that cardiac rhythm management devices are often required at an early age and expose patients to device-related complications. The present study drew upon four decades of experience at a tertiary adult congenital heart disease ACHD center and aimed to investigate the indication for cardiac implantable electronic devices (CIEDs) and predictors of late device-related complication requiring re-intervention. Methods: A retrospective review of pacing records of ACHD patients over forty years was carried out. The primary outcome measure was device related complication requiring re-intervention. Results: Between 1970 and 2009, 238 structural CHD patients who received CIEDs with follow-up data were identified (structural group). As a comparator group, 98 patients with congenital conduction disease or long QT syndrome with a structurally normal heart (electrical group) were included in the study. During a mean follow-up of 9.6 ± 8.5years, 72 (21%) patients (44 structural group, 28 electrical group) required ≥ 1 re-intervention due to device related complications. Multivariate analysis showed that age at the time of device implant was an independent predictor of late device-related complications (HR 0.77, 95% CI 0.60–0.98, p = 0.04). Sub-analysis of the structural group showed that ACHD complexity (Bethesda guideline) was the only predictor late device-related complication in the structural group (HR 2.96, 95% CI: 1.67–5.26, p < 0.01). Conclusion: Increasing age at device implant was inversely associated with late device-related complications. ACHD patients with complex anatomy are at increased risk of device-related complications at mid and long-term follow-up.